2020
DOI: 10.1016/j.cjco.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Access to 3-Dimensional Printing in the Context of Congenital Heart Disease: An International Physician Survey Study

Abstract: Background Three-dimensional (3D) printing is a new technology capable of producing patient-specific 3D cardiac models. Methods A cross-sectional survey of pediatric cardiologists was conducted. Members of the Canadian Pediatric Cardiology Association and Congenital Cardiac Interventional Study Consortium were invited to participate. A questionnaire was distributed using Research Electronic Data Capture between May and September 2019. Results were analyzed using descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In all of the 19 studies feedback and results on the use of 3D models for communication were positive, irrespective of the type of respondent or type of communication. Illmann et al found that of the 85% of clinicians who found benefit from the models, 80% of them believed they would facilitate communication with colleagues and 72% believed they would be useful in communication with parents or families [ 17 ]. In an orthopedics study, patients were asked ‘How much does the CT or 3D-printing model help you to gain a better communication with doctors?’ [ 18 ] and patients in the 3D-printing group rated the 3D-printed model an average of 8.5 compared with 6.5 for those rating the CT scans.…”
Section: Resultsmentioning
confidence: 99%
“…In all of the 19 studies feedback and results on the use of 3D models for communication were positive, irrespective of the type of respondent or type of communication. Illmann et al found that of the 85% of clinicians who found benefit from the models, 80% of them believed they would facilitate communication with colleagues and 72% believed they would be useful in communication with parents or families [ 17 ]. In an orthopedics study, patients were asked ‘How much does the CT or 3D-printing model help you to gain a better communication with doctors?’ [ 18 ] and patients in the 3D-printing group rated the 3D-printed model an average of 8.5 compared with 6.5 for those rating the CT scans.…”
Section: Resultsmentioning
confidence: 99%
“…Technologies discussed in the literature include computer-based learning (eg, videos, animations, multimedia simulation software, 3D models, and 3D computer graphics), 3D printed models, and extended realities (stereoscopic videos, virtual reality, and augmented reality). The tools are valuable teaching and learning aids [ 2 - 13 ] but are underused [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…All that said, 3D printing is not universally available and can be expensive ( 11 ). Emerging technology allows visualization of complex cardiac anatomy virtually without the need for 3D printing ( 12 ).…”
mentioning
confidence: 99%